Nature-based Solutions in the Municipal Vulnerability Preparedness Program. - Clarren, Sarah.; Rodriguez, Minerva Ciaffone.; Ruderman, Tess.; Tshering, Namgay P.; Webster, Jordan. (Tufts University. Tisch Library., 2019)
2019 M.A. in Urban and Environmental Policy and Planning Field Project. Client: MassAudubon and The Nature Conservancy.